FACTORS AFFECTING THE LEVEL OF STOCK UNDERPRICING IN NON-FINANCIAL COMPANIES - Denni Tanoyo; Rizka Indri Arfianti (Management and Leadership Study Programme, 2022)
This study aims to predict the factors affecting the stock’s underpricing in non-financial companies of the Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) for the period 2017 – 2019. Compared to previous research, this study provides all the non -financial companies that conduct IPOs. In 2017 to 2019, there are 141 non-financial companies that conduct IPO. This research uses judgment sampling so there are only 131 companies that qualify. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, t-test, f-test, and R square. The result showed that return on assets, firm size, underwriter’s reputation, and auditor’s reputation have a negative effect and significant on the level of stock underpricing, meanwhile, financial leverage has a positive effect and significant on the level of stock underpricing.